2012
DOI: 10.1039/c2ra20266b
|View full text |Cite
|
Sign up to set email alerts
|

Structural refinement, growth process, photoluminescence and photocatalytic properties of (Ba1-xPr2x/3)WO4 crystals synthesized by the coprecipitation method

Abstract: Barium praseodymium tungstate (Ba 1-x Pr 2x/3 )WO 4 crystals with (x = 0, 0.01, and 0.02) were prepared by the coprecipitation method. These crystals were structurally characterized by X-ray diffraction (XRD), Rietveld refinements, Fourier-transform Raman (FT-Raman) and Fourier-transform infrared (FT-IR) spectroscopies. The shape and size of these crystals were observed by field emission scanning electron microcopy (FE-SEM). Their optical properties were investigated by ultraviolet visible (UV-vis) absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(24 citation statements)
references
References 124 publications
2
22
0
Order By: Relevance
“…This phenomenon can be explained by new electronic levels related to additional 4f orbitals of Eu 3 þ ions. Cavalcante et al [22] achieved a significant reduction in E gap values (from 4.9 to 3.82 eV) upon the replacement of Ba 2 þ by Pr 3 þ in the BaWO 4 lattice. They reported that Pr 3 þ ions induce the appearance of a new intermediary energy level within the optical band gap, since the praseodymium contributes 4f orbitals, while the barium exhibits 6 s orbitals in the valence band.…”
Section: Ultraviolet-visible Absorption Spectroscopy Analysismentioning
confidence: 97%
“…This phenomenon can be explained by new electronic levels related to additional 4f orbitals of Eu 3 þ ions. Cavalcante et al [22] achieved a significant reduction in E gap values (from 4.9 to 3.82 eV) upon the replacement of Ba 2 þ by Pr 3 þ in the BaWO 4 lattice. They reported that Pr 3 þ ions induce the appearance of a new intermediary energy level within the optical band gap, since the praseodymium contributes 4f orbitals, while the barium exhibits 6 s orbitals in the valence band.…”
Section: Ultraviolet-visible Absorption Spectroscopy Analysismentioning
confidence: 97%
“…Barium tungstate (BaWO 4 ) crystals have attracted significant interest from many research groups due to their potential applications in scintillation devices, batteries, capacitors, photocatalysts, and, in particular, photoluminescent materials [1][2][3][4][5][6]. In recent years, various synthetic methods have been used to produce BaWO 4 crystals, such as co-precipitation (CP), sol-gel, modified Pechini, solid state reaction, solution route, Czochralski, sonochemical, and hydrothermal techniques [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…According to Longo et al [8], the emission in the red spectrum is most likely related to the [AgOy] clusters. In this manner, an increase in the violet PL emission in the Ag 2 W 0.50 Mo 0.50 O 4 sample is also related to order-disorder effects, which significantly influence the luminescence properties of the tungstates [37].…”
Section: Photoluminescence Emission Of Ag 2 W 1-x Mo X O 4 Crystalsmentioning
confidence: 88%